Application of Inquiry Methods to Academic Achievement of Children with Attention Deficit Hyperactivity Disorder in Inclusive Schools - Eko Wahyu Wibowo; Mumpuniarti Mumpuniarti (Department of Special Education, 2019)
This study is aimed at examining the inquiry method usage on the academic achievement of children with Attention Deficit Hyperactivity Disorder (ADHD) in Inclusive Schools. The method used is a quasi-experiment with the design of one group pretest and posttest. The subjects were 4th grade students of Inclusive Elementary Schools. The results of the study prove that the inquiry method can help the academic achievement of ADHD children in inclusive primary schools. This is indicated by a change in scores on academic ability by 90%. During the inquiry method usage, ADHD children are not only able to understand the learning material delivered in the classroom but also show a high enthusiasm, active, and serious attitude in participating the learning process in Inclusive Primary Schools.